Buffer Overflow: Proof Of Concept Implementation - , Dr.Sushma Jain, Pooja Rani (International Journal of Scientific Research and Management (IJSRM), 2017)
The Information security vulnerabilities have become a significant concern for the computer users. Buffer Overflows are responsible for many vulnerabilities in the operating system and the application programs. These are mainly results of the programming errors done by the programmers during the coding phase. They can cause serious problems in various categories of software systems. In this work the Proof of concept for the Buffer Overflow attacks has been implemented and analyzed for different types of the application using the Windows XP and Linux Operating System and after that the results are described.